2018
DOI: 10.1016/j.jaim.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Tinospora cordifolia extract prevents cadmium-induced oxidative stress and hepatotoxicity in experimental rats

Abstract: BackgroundCadmium (Cd) pollution is of serious concern due to its toxic effects in both humans and animals. The study investigates the protective effect of Tinospora cordifolia stem methanolic extract (TCME) on Cd induced hepatotoxicity.Objective(s)The objective of the study was to explore the hepatoprotective effects of T. cordifolia extract.Materials and methodsRats were administered orally with Cd (5 mg/kg) and TCME (100 mg/kg) for 28 days. At the end of the treatment period, serum and liver tissues homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 52 publications
2
11
0
1
Order By: Relevance
“…Superoxide dismutase (SOD) is an antioxidant enzyme which catalyzes the dismutation of superoxide anions (O 2-) into H2O2 and molecular oxygen (21). It plays important protective roles against cellular and histological damage induced by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase (SOD) is an antioxidant enzyme which catalyzes the dismutation of superoxide anions (O 2-) into H2O2 and molecular oxygen (21). It plays important protective roles against cellular and histological damage induced by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent antioxidant properties were reported with the ethanolic and n-butanol fractions of T. cordifolia extracts [34]. They have been shown to stabilize the antioxidant status of heart [35], liver and kidney [30,36,37] and inhibit the superoxide, hydroxyl radicals and lipid peroxidation. Studies showed that the methanolic extracts of T. cordifolia-stems prevented cadmium-induced cardiotoxicity, hepatotoxicity and nephrotoxicity by their antioxidant activity via modulation on the cellular antioxidant status of antioxidant enzymes such as superoxide dismutase, catalase, glutathione-s-transferase, glutathione peroxidase and GSH levels [30,35,37].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…4 Therapeutic Properties T. cordifolia T. cordifolia has been reported to have antioxidant, anticancer, radio protective, antidiabetic, antidote, antimicrobial, antiallergic, antihyperglycemic, antileprotic, anti-inflammatory, antihyperlipidemic and immunomodulatory properties [30].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The individual effect of guduchi (Tinospora cardifolia) against carbon tetrachloride-induced hepatic damage, cadmium induce oxidative stress and hepatotoixicity [12] and gentamycininduced renal toxicity has been studied [13,14]. Similarly, the individual effect of punarnava (Boerhavia diffusa) on gentamicin-induced nephrotoxicity and thioacetamide intoxicated rats has been studied [15,16].…”
Section: Introductionmentioning
confidence: 99%